2014
DOI: 10.1188/14.cjon.s2.7-11
|View full text |Cite
|
Sign up to set email alerts
|

Setting the Bar: Developing Quality Measures and Education Programs to Define Evidence-Based, Patient-Centered, High-Quality Care

Abstract: In 2008, the Oncology Nursing Society (ONS) initiated a multi-year project to develop and test quality measures in areas judged by oncology nurses as high-priority opportunities to improve quality of life for patients across the cancer continuum, and to provide education to oncology nurses on how to achieve high-quality care. Supported through a grant to the ONS Foundation by the Breast Cancer Fund of the National Philanthropic Trust, two teams of expert nurses convened to review the literature and draft poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Instead, clinicians should be adopting a proactive approach in the assessment and intervention of BCRL. Through participation in the ONS Foundation-supported Breast Cancer Survivorship (BCS) Quality Measures Set pilot study (Fessele, Yendro, & Mallory, 2014), the authors found the assessment of lymphedema practices at the Springfield Clinic to be less than optimal. The pilot project compelled the authors to look at the current process and workflow related to the care of patients with breast cancer, particularly in the area of lymphedema.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, clinicians should be adopting a proactive approach in the assessment and intervention of BCRL. Through participation in the ONS Foundation-supported Breast Cancer Survivorship (BCS) Quality Measures Set pilot study (Fessele, Yendro, & Mallory, 2014), the authors found the assessment of lymphedema practices at the Springfield Clinic to be less than optimal. The pilot project compelled the authors to look at the current process and workflow related to the care of patients with breast cancer, particularly in the area of lymphedema.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership is about building relationships, and ONS provides a forum to join together experts of all oncology practice backgrounds, which is also the case with the ONS Foundationsupported Breast Cancer Care (BCC) Quality Measures Set pilot study (Fessele, Yendro, & Mallory, 2014). The VHA's unique role afforded diversity with the population of women veterans and geographic diversity, with women from rural to urban and large to small settings.…”
mentioning
confidence: 98%
“…One of the Quality measures was to ascertain the percentage of patients beginning chemotherapy who received counseling about exercise as an intervention to combat fatigue. 14 …”
Section: 5mentioning
confidence: 99%
“…1,15,16 According to the ONS, about 10% of patients with breast cancer received recommendation to exercise in order to reduce their fatigue. 14 Nurses' management of illnesses is influenced by their beliefs about the effectiveness of the treatment. Treatment beliefs of nurses affected the degree to which they managed patients undergoing cervical cancer screening.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%